Strategi Peningkatan Volume Muatan Kapal Roro Trayek Makassar-Jakarta di PT Bumi Lintas Tama Kalla Lines - Rusnaedi Rusnaedi; Sudarman Sudarman; A.Murtafiah; Arif Fuddin Usman; Andi Annisa Talha (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to determine the factors that affect the low volume of cargo and get the right action strategy to increase the volume of cargo of RollOn–RollOff (RoRo) Makassar-Jakarta route at PT Bumi Lintas Tama Kalla Lines. The type of data used in this research is quantitative data, namely about the main size of the ship (LOA, LBP, B, H and T), the ship's cargo capacity, the size of the ship's loading space, the number of ship decks, determining the internal and external factors that influence the handling of Roro Ferry shiploads with interviews and questionnaires and Questionnaire Forms. Using the method with the results obtained from the calculation of the load factor and the determination of the fishbone diagram factors to get the root cause of the lack of RoRo ship cargo volume. The sample in this study were 50 respondents consisting of practitioners at the Port and AMI Maritime Polytechnic Lecturers in Makassar. The results of this study indicate that the company adopts a conventional system that focuses on one side, namely incoming cargo or the Jakarta-Makassar route. In addition, the use of SWOT analysis found that the situation experienced by PT Bumi Lintas Tama is in quadrant IV, indicating an unfavorable situation with various internal threats and weaknesses. It is recommended to focus on strengthening internal strengths and overcoming weaknesses. As for its operational efficiency and performance, it should adopt a more holistic approach and consider using methods other than the fishbone method.